Effects of Bifidobacterium and rosuvastatin on metabolic-associated fatty liver disease via the gut–liver axis - Xue Ran; Ying-jie Wang; Shi-gang Li; Chi-bing Dai (Lipids in Health and Disease)
Abstract Background/aims Research has indicated that treatment with rosuvastatin can improve liver pathology in metabolic-associated fatty liver disease (MAFLD) patients and that treatment with Bifidobacterium can improve MAFLD. Therefore, the effects of Bifidobacterium, rosuvastatin, and their combination on related indices in a rat model of diet-induced MAFLD need to be investigated. Methods Forty rats were divided into five groups: the normal diet group (N), high-fat diet (HFD) model group (M), HFD + probiotic group (P), HFD + statin group (S), and HFD + probiotic + statin group (P-S). To establish the MAFLD model, the rats in Groups M, P, S, and P-S were fed a HFD for 8 weeks. The treatments included saline in Group N and either Bifidobacterium, rosuvastatin, or their combination in Groups P, S, and P-S by intragastrical gavage. After 4 weeks of intervention, the rats were euthanized, and samples were harvested to analyze gastrointestinal motility and liver function, pathological changes, inflammatory cytokine production, and the expression of proteins in key signaling pathways. Results HFD feeding significantly increased the body weight, liver index, and insulin resistance (IR) index of the rats, indicating that the MAFLD model was successfully induced. Bifidobacterium reduced the liver of MAFLD rats, while Bifidobacterium with Rosuvastatin decreased the liver index, IR index, and levels of aspartate aminotransferase and alanine aminotransferase in MAFLD rats. The MAFLD model showed altered expression of proteins in signaling pathways that regulate inflammation, increased production of inflammatory cytokines, an elevated MAFLD activity score (MAS), and pathological changes in the liver. The MAFLD model also showed reduced relative counts of intestinal neurons and enteric glial cells (EGCs), altered secretion of gastrointestinal hormones, and slowed gastrointestinal emptying. Bifidobacterium, rosuvastatin, or their combination inhibited these various changes. HFD feeding changed the rats’ gut microbiota, and the tested treatments inhibited these changes. These results suggest that the gastrointestinal motility disorder and abnormal liver function in MAFLD rats may be related to a reduction in Escherichia-Shigella bacteria and an increase in Asticcacaulis bacteria in the gut microbiota and that the improvement in liver function induced by Bifidobacterium plus rosuvastatin may be related to increases in Sphingomonas and Odoribacter bacteria and a decrease in Turicibacter bacteria in the gut microbiota. Conclusions The combined use of Bifidobacterium and rosuvastatin could better regulate the gut microbiota of MAFLD model rats, promote gastrointestinal emptying, and improve liver pathology and function than single treatment with Bifidobacterium or rosuvastatin. This provides a better strategy for the treatment of MAFLD.